Bee pollen as a functional ingredient in bread: an exploratory study based on attitudes and expectations of Brazilian consumers - Pestana M. da Silva, Heloisa (2024)
This study investigated consumers' perceptions of adding bee pollen to bread. An attitude questionnaire composed of 48 statements related to "general health," "light products," "natural products," "salty products," "food as a reward," "pleasure," and "food neophobia" was answered by the participants, who indicated their level of agreement with each statement according to a 5-point Likert scale, ranging from (1) "totally disagree" to (5) "totally agree." A check-all-that-apply (CATA) questionnaire was also employed to characterize 12 visual stimuli. The creation of stimuli was carried out using a factorial design, resulting in 12 images of bread. Three clusters of consumers were identified, each associating positive attributes with stimuli containing bee pollen, regardless of the health claim, while negative attributes were associated with stimuli without added pollen. The main positive drivers of liking were "I would buy," "attractive," "pleasant color," "healthy," "light," and "natural." On the other hand, the negative drivers of liking were "unattractive," "I don't like it," "I wouldn't buy," "hard," and "unpleasant color." This study provides valuable information for developing healthier bread using natural ingredients with bioactive compounds, such as bee pollen.